Advances on the use of the parasitoid Cephalonomia stephanoderis for the control of the coffee berry borer, Hypothenemus hampei - BENAVIDES-MACHADO, PABLO; BUSTILLO-PARDEY, ALEX E.; CECILIA-MONTOYA, ESTHER (Revista Colombiana de Entomología, 1994)
The coffee berry borer, Hypothenemus hampei (Ferrari), is an introduced insect that has arrived into Colombia without natural enemies. In its home land (Africa), there are several parasitoids which regulate the borer populations. Recently the parasitoid from Ivory Coast, Cephalonomia stephanoderis Betrem, was introduced and a method for mass production has been developed. In this research, an evaluation was conducted to determine the effect of massive releases of this wasp against H. hampei populations in four coffee farms in Nariño, located at different altitudes (1,080, 1,240, 1,484, 1,630 masl). At each farm infested by the borer, two plots were selected, one to release the parasitoid and the other as a control plot. The released parasitoids numbers varied according to the borer infestation, releasing one wasp per 2-3 infested berries. The total number of parasitoids released in all the plots was 272,500 between October 1991 and June 1992. Field evaluations on borer infestation and parasitism among all the plots varied from less than 10% up to 65%. The increase of parasitism was correlated with higher altitudes parasitism was lower, which can be explained by a temperature effect, and the lower borer populations. This study allows to conclude that C. stephanoderis can be used as a complement in a coffee berry borer control program since once is released it gets established in the Colombian coffee ecosystem, it has the capacity of dispersion and under high levels of borer populations it can reach high levels of parasitism. It remains to study its effect under low levels of borer population.